Managing Capital Budget Projects: A Preemptive Audit Approach (Book). - Watne, Donald A.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Managing Capital Budget Projects: A Preemptive Audit Approach," by Felix Pomeranz.